STRATEGI PEMBELAJARAN MENGGUNAKAN MEDIA VISUAL DAN PUZZLE UNTUK MENGURANGI HIPERAKTIVITAS ANAK AUTIS DI SKHN 02 LEBAK - Silvi Gustavio Edward; Yahdinil Firda Nadirah (STKIP Subang, 2025)
Hyperactivity in children with autism causes difficulties in focusing, sitting still, and following learning instructions in the classroom. This study aims to describe learning strategies through visual media and puzzle-based activities to reduce hyperactive behavior in autistic children at SKhN 02 Lebak. A descriptive qualitative approach was used through interviews with an experienced teacher. The findings show that visual aids such as pictures, daily activity schedules, and simple videos help children understand instructions and reduce impulsive behavior. Puzzle activities are effective in increasing children’s focus, regulating emotions, and redirecting excessive energy. The combination of visual media and puzzles creates a more structured, calm, and enjoyable learning environment. This strategy is recommended to be applied in special schools and inclusive settings with adjustments to individual characteristics.The results of the study indicate that the use of visual media such as activity pictures, visual symbols, daily visual schedules, and simple instructional videos helps children understand learning instructions more clearly and reduces anxiety caused by uncertainty in classroom activities. Visual media provide structure and predictability, which are essential for children with autism. Puzzle-based activities are effective in increasing concentration, emotional regulation, and task persistence. Puzzle activities also function as a redirection strategy to channel excessive energy into meaningful and enjoyable tasks. In addition, the application of positive reinforcement in the form of praise and simple rewards strengthens adaptive behavior and increases learning motivation. Overall, the combination of visual media and puzzle activities creates a more structured, calm, and engaging learning environment for autistic children. This strategy is recommended for implementation in special schools and inclusive educational settings with adjustments based on individual child characteristics.